2010
DOI: 10.1186/cc9234
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pathogen detection from clinical samples by real-time polymerase chain reaction using a sepsis pathogen DNA detection kit

Abstract: IntroductionSepsis is a serious medical condition that requires rapidly administered, appropriate antibiotic treatment. Conventional methods take three or more days for final pathogen identification and antimicrobial susceptibility testing. We organized a prospective observational multicenter study in three study sites to evaluate the diagnostic accuracy and potential clinical utility of the SeptiFast system, a multiplex pathogen detection system used in the clinical setting to support early diagnosis of blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
79
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 20 publications
9
79
0
2
Order By: Relevance
“…In contrast, in the case of blood culture, antibiotic administration reduced the probability of pathogen isolation by half. This finding is consistent with results reported by other researchers 8,21,33 and supports the usefulness of SeptiFast in cases where antibiotic therapy has already been started and shows its advantages over blood cultures.…”
Section: Discussionsupporting
confidence: 83%
“…In contrast, in the case of blood culture, antibiotic administration reduced the probability of pathogen isolation by half. This finding is consistent with results reported by other researchers 8,21,33 and supports the usefulness of SeptiFast in cases where antibiotic therapy has already been started and shows its advantages over blood cultures.…”
Section: Discussionsupporting
confidence: 83%
“…It is a relatively rapid molecular method allowing detection of sepsis pathogens in approximately 6 h. There are several studies to date about diagnostic feasibility and potential clinical utility of SF [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Fewer studies have evaluated this assay in routine clinical practice regarding impact on therapy [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…The targets for amplification are the internal transcribed sequences between the bacterial 16S and 23S genes, and the fungal 18S and 5.6S rRNA genes (Lehmann et al, 2008). In several studies it has been demonstrated that this test can be more sensitive than blood culture for the diagnosis of sepsis in different settings (Mancini et al, 2008;Yanagihara et al, 2010), especially in patients already receiving antibiotics (Vince et al, 2008). Moreover, in nonsepsis infections, such as bacterial endocarditis, joint or other deep infections, it is often difficult to isolate bacterial agents from clinical specimens, especially if patients undergo antibiotic treatment.…”
Section: Introductionmentioning
confidence: 99%